2000
DOI: 10.1104/pp.123.1.363
|View full text |Cite
|
Sign up to set email alerts
|

Fruit-Localized Phytochromes Regulate Lycopene Accumulation Independently of Ethylene Production in Tomato

Abstract: We show that phytochromes modulate differentially various facets of light-induced ripening of tomato fruit (Solanum lycopersicum L.). Northern analysis demonstrated that phytochrome A mRNA in fruit accumulates 11.4-fold during ripening. Spectroradiometric measurement of pericarp tissues revealed that the red to far-red ratio increases 4-fold in pericarp tissues during ripening from the immature-green to the red-ripe stage. Brief red-light treatment of harvested mature-green fruit stimulated lycopene accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 25 publications
9
157
1
2
Order By: Relevance
“…The involvement of phytochromes in the control of carotenoid accumulation and PSY gene expression in different plant species, including tomato, maize, and rice (12,13,33), along with the presence of G-boxes in the promoters of light-responsive maize and rice PSY genes (13,34), suggest that the participation of PIFs in the light-mediated regulation of PSY gene expression might be a general mechanism in plants.…”
Section: Carotenoid Levels Correlate With Pif-mediated Changes In Psymentioning
confidence: 99%
“…The involvement of phytochromes in the control of carotenoid accumulation and PSY gene expression in different plant species, including tomato, maize, and rice (12,13,33), along with the presence of G-boxes in the promoters of light-responsive maize and rice PSY genes (13,34), suggest that the participation of PIFs in the light-mediated regulation of PSY gene expression might be a general mechanism in plants.…”
Section: Carotenoid Levels Correlate With Pif-mediated Changes In Psymentioning
confidence: 99%
“…3, No. 2 (2016) fruit-localized phytochromes, sensitive to R/ FR ratio, mediate lycopene accumulation in the berries (Alba et al 2000). Sampling time had a highly significant effect on the carotenoid content.…”
Section: Total Carotenoid Contentmentioning
confidence: 97%
“…High temperatures 32 and excessive light intensity were found to affect lycopene synthesis and degradation in tomato and grapefruit 26 29 . Alba et al 30 found that red light will stimulate carotenoid accumulation in tomato, whereas far-red light blocks its accumulation. In contrast, Vogele 31 observed that lycopene synthesis in watermelon is not affected by temperatures in the range of 20 to 37 , but its content is reduced at temperatures between 4 and 21 in red grapefruit 32,33 .…”
Section: Carotenoid Biosynthesismentioning
confidence: 99%